CONTEXTUAL TEACHING AND LEARNING PADA ARITMATIKA SOSIAL - M. Anang Taufik; Mulyoto Mulyoto; Sunardi Sunardi; Nunuk Suryani (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2019)
The purpose of this research is to know and investigate the difference of students’ ability in doing social arithmetic and the implementation of contextual teaching and learning model in experimental class and students’ ability in doing social arithmetic that taught by applying tutor method in control class. This research is classified as a quasi-experimental design which is used pre and posttest control group design. The sample of this research was eight B grade students as experimental class and eight grade A students as a control class. This research took place at junior High School (SMP) Negeri 2 Gondang, Bojonegoro, East java. This research applied random sampling technique. The sum of subject of the research was about 56 students which consist of 28 students from control class and 28 students from experimental class. The result of the research shows that there is difference in implementation of two different learning models. The implementation of contextual teaching and learning model is better than tutor model. It can be proved from the mean score of posttest in experimental class. It was 75.89 while in control class was about 71.96. It can be said that there was significant difference about 3.93. It can be concluded that contextual teaching and learning (CLT) model can improve students’ ability in doing social arithmetic better than tutor model. Tujuan dari penelitian ini adalah untuk mengetahui perbedaan kemampuan siswa menyelesaikan soal aritmatika sosial dari implementasi model pembelajaran Contextual Teaching and Learningdi kelas eksperimen dibandingkan dengan kemampuan siswa menyelesaikan soal aritmatika sosial dengan model pembelajaran ceramah di kelas kontrol. Jenis penelitian ini adalah quasi eksperimen dengan desain penelitian pre tes posttes control group design. Sample yang digunakan dalam penelitian ini adalah siswa SMP Negeri 2 Gondang Bojonegoro Jawa Timur kelas VIII B sebagai kelas eksperimen dan kelas VIII A sebagai kelas kontrol yang ditentukan dengan teknik random sampling. Subjek penelitian ini terdiri dari 56 siswa di kelas eksperimen 28 siswa di kelas kontrol sebanyak 28 siswa. Berdasarkan hasil penelitian menunjukkan perbedaan bahwa penerapan model pembelajaran Contextual Teaching and Learning lebih baik dari model pembelajaran ceramah yang selama ini digunakan. Hal ini dapat dilihat dari nilai rata-rata post tes di kelas eksperimen adalah 75,89 dikelas kontrol nilai post tes adalah 71,96 sehingga didapat perbedaan sebesar 3,93. Kesimpulan hasil penelitian ini adalah bahwa model pembelajaran Contextual Teaching and Learning (CTL) dapat meningkatkan kemampuan siswa dalam menyelesaikan aritmatika sosial lebih baik daripada model pembelajaran ceramah.